2021
DOI: 10.1038/s41598-021-02545-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Norway spruce ecotypes assessed by GBS-derived SNPs

Abstract: We investigated the genetic structure of three phenotypically distinct ecotypic groups of Norway spruce (Picea abies) belonging to three elevational classes; namely, low- (acuminata), medium- (europaea), and high-elevation (obovata) form, each represented by 150 trees. After rigorous filtering, we used 1916 Genotyping-by-Sequencing generated SNPs for analysis. Outputs from three multivariate analysis methods (Bayesian clustering algorithm implemented in STRUCTURE, Principal Component Analysis, and the Discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 100 publications
2
8
0
Order By: Relevance
“…Low-elevation ( acuminata ) has a wide crown with long branches, while high-elevation ( obovata ) has a narrow crown with short branches pointing down. Genetic differences among the putative ecotypes were recently confirmed by Korecký et al (2021) . There are emerging pieces of evidence that some physiological traits also differ among the ecotypes, Tomášková et al (2021) found that parameters describing structural indicators of PSII in the thylakoid membrane (calculated from the OJIP test) distinguished obovata ecotype.…”
Section: Introductionmentioning
confidence: 82%
“…Low-elevation ( acuminata ) has a wide crown with long branches, while high-elevation ( obovata ) has a narrow crown with short branches pointing down. Genetic differences among the putative ecotypes were recently confirmed by Korecký et al (2021) . There are emerging pieces of evidence that some physiological traits also differ among the ecotypes, Tomášková et al (2021) found that parameters describing structural indicators of PSII in the thylakoid membrane (calculated from the OJIP test) distinguished obovata ecotype.…”
Section: Introductionmentioning
confidence: 82%
“…Car e et al (2018) used genetic analysis of microsatellites and revealed that autochthonous high-elevation-type stands from the Thuringian Forest, Ore Mountains, and Harz Mountains (Germany) were not differentiated from the neighbouring allochthonous lowelevation-type stands, although differentiation was detected when comparing these populations with an old-growth relict narrow-crowned population of "Schlossbergfichte" in Thuringia. In addition, an association of candidate genes related to circadian rhythms with crown morphotypes and altitudinal adaptation in these spruce populations from Germany was described in Car e et al (2020), and more recently a shallow population genetic structure and differentiation was described between low and medium elevation morphotypes, on the one hand, and high elevation morphotypes on the other (Koreck y et al 2021). But beyond crown morphology, other adaptive phenotypic traits related to elevation, such as phenology or budburst, have not been targeted in association studies of Norway spruce.…”
Section: Introductionmentioning
confidence: 85%
“…And it was found that the highest number of SNP markers but the lowest genetic diversity value was obtained under the first set of criteria (i.e., MAF > 0.01, Call rate > 0.9), thus indicating that setting of MAF filtering criteria had a greater effect on the number of SNP markers obtained. The filtering criteria for Chinese fir SNP selection in this study were more stringent than those implemented for Picea abies (Koreckýet al, 2021), Ulmus pumila (Lyu et al, 2020), and other Chinese firs (Zheng et al, 2019). Principal component analysis where PC1 and PC2 represent the first and second principal components, respectively.…”
Section: Reliability Of Rad-seq For Simplified Sequencingmentioning
confidence: 99%
“…The RAD-seq simplified sequencing technique is developed to generate a wider range of SNP markers. It is a cost-effective genotyping technique that detects variant information on a genome-wide scale, but the quality of the obtained SNPs is usually variable and the lack of stringent filtering can seriously affect subsequent analyses (Koreckýet al, 2021). The initial 27,283,139 SNP markers obtained after the reference genome alignment, and implementation of strict filtering criteria helped obtaining highquality SNP markers and finally only 1.26% of SNPs were retained as high-quality SNP markers.…”
Section: Reliability Of Rad-seq For Simplified Sequencingmentioning
confidence: 99%
See 1 more Smart Citation